Islamic Communication and Mental Health: A Literature Review of Spiritual Approaches to Managing Stress and Anxiety - Mahmoud Galander (PT. Berkah Smart Academica, 2026)
The rising prevalence of global stress and anxiety necessitates a holistic and culturally sensitive intervention model, particularly within Muslim communities where mental health issues often carry religious stigma. Objective: This study aims to synthesize contemporary academic literature regarding the role of Islamic communication—both transcendental (vertical) and interpersonal (horizontal)—as a spiritual instrument in mental health management. Methods: A Systematic Literature Review (SLR) was conducted using the PRISMA protocol, analyzing 45 reputable articles from Scopus, Sinta, and Garuda databases published between 2021 and 2025. Results: The findings indicate that Islamic communication techniques, such as dhikr (remembrance), du’a (prayer), and tawakkul (resignation), function as effective proactive coping mechanisms that reduce cortisol levels and stabilize emotions through spiritual-based cognitive restructuring. Conclusion: The integration of spiritual communication into clinical psychological services not only enhances healing efficacy but also significantly deconstructs the social stigma surrounding mental disorders. This study provides a vital framework for developing mental health intervention models that harmonize religious wisdom with modern medical standards.